2015
DOI: 10.1111/phn.12216
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sexual Health Professionals in Developing a Shared Concept of Risky Sexual Behavior as it Relates to HIV Transmission

Abstract: “Risky sexual behavior” accounts for the majority of new HIV infections regardless of gender, age, geographic location, or ethnicity. The phrase, however, refers to a relatively nebulous concept that hampers development of effective sexual health communication strategies. The purpose of this paper is to propose development of a shared conceptual understanding of “risky sexual behavior.” We reviewed multidisciplinary HIV/AIDS literature to identify definitions of risky sexual behavior. Both the linguistic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Limiting a woman’s access to birth control could also lower her sexual autonomy, potentially placing her at higher risk for HIV. The risk for transmission is greatest if a woman or her partner engage in sexual risk behaviors such as partner concurrency or sex with multiple partners [7]. Thus, it is critical for researchers to examine the acceptability of innovative women-controlled HIV-prevention methods among women at risk for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Limiting a woman’s access to birth control could also lower her sexual autonomy, potentially placing her at higher risk for HIV. The risk for transmission is greatest if a woman or her partner engage in sexual risk behaviors such as partner concurrency or sex with multiple partners [7]. Thus, it is critical for researchers to examine the acceptability of innovative women-controlled HIV-prevention methods among women at risk for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, items on the SRS do not account for the differences in risky sexual behaviors as they correspond to the gender identities of participants’ sexual partners and participant’s role (i.e., insertive or receptive partner) in the sexual activity; the latter may be particularly relevant for respondents in the present study who identified as transgender bisexual men. Consequently, researchers are encouraged to consider alternative methods of comprehensively operationalizing risky sexual behaviors among sexual minority individuals broadly and bisexual individual in particular that are both sex-positive (i.e., does not stigmatize “promiscuity”) and inclusive (e.g., considers consensually nonmonogamous relationships; Brawner, Alexander, Fannin, Baker, & Davis, 2016). Moreover, although this study is the first of its kind to assess bisexual men’s risky sexual behaviors via a comprehensive minority stress theory framework, future studies should also consider the association of bisexual minority stressors and substance use with additional dimensions of sexual health, such as sexual satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of awareness of the high incidence of genital injuries resulting from consensual and non-consensual sex51, HIV prevention trials have not considered the potential impact of genital trauma as an independent risk factor for HIV acquisition. Moreover, evaluation of genital trauma in large clinical trials designed to prevent HIV acquisition is complicated due to numerous factors52.…”
Section: Discussionmentioning
confidence: 99%